2007
DOI: 10.1016/j.ydbio.2007.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Caught in the evolutionary act: Precise cis-regulatory basis of difference in the organization of gene networks of sea stars and sea urchins

Abstract: The regulatory control of otxbeta1/2 in the sea urchin Strongylocentrotus purpuratus and the sea star Asterina miniata provides an exceptional opportunity to determine the genomic basis of evolutionary change in gene regulatory network (GRN) architectures. Network perturbation analyses in both taxa show that Otx regulates the transcription factors gatae and krox/blimp1 and both of these transcription factors also feed back and regulate otx. The otx gene also autoregulates. This three way interaction is an exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 41 publications
2
58
1
Order By: Relevance
“…Sequencing confirmed successful integration (Yu et al, 2000). Constructs were prepared and injected as described previously (Hinman et al, 2007).…”
Section: Bac Construct Development and Injectionsmentioning
confidence: 99%
“…Sequencing confirmed successful integration (Yu et al, 2000). Constructs were prepared and injected as described previously (Hinman et al, 2007).…”
Section: Bac Construct Development and Injectionsmentioning
confidence: 99%
“…However, highly conserved cis-regulatory sequences account for only a minor fraction of the large number of genomic cis-regulatory modules likely to exist in animal genomes (8), and cis-regulatory comparisons at significant evolutionary distance often reveal conserved control functions even when sequence conservation is not detectable across the cis-regulatory module. In such examples, where functional assays carried out by insertion of known cis-regulatory modules into the genomes of different species reveal conserved function, it is found that only the specific transcription factor (TF) target sites are retained, spaced in nonconserved DNA sequence, often in diverse site order and number (9)(10)(11). Whether the DNA sequence of the cis-regulatory module is largely conserved or not, if the function remains the same, the implication is that the set of TFs to which its target sites respond are largely the same.…”
mentioning
confidence: 99%
“…A comparative analysis of the endomesoderm GRN between sea urchins and sea stars showed that much of the early circuitry responsible for activation of endoderm is conserved, despite an evolutionary separation from a common ancestor more than 500 million years ago (Hinman et al, 2003;Hinman et al, 2007). More distant comparisons show that many of the genes that operate early in the sea urchin GRN are also likely to govern the activation of GRNs in hemichordates (Lowe et al, 2006;Lemons et al, 2010), and components of the early network may also be conserved in other deuterostomes.…”
Section: The Evolution Of Grnsmentioning
confidence: 99%